2015
DOI: 10.1186/s13054-015-0832-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of apolipoprotein A-I and high-density lipoprotein can predict organ failure in acute pancreatitis

Abstract: IntroductionPredicting severity of pancreatitis is an important goal. Clinicians are still searching for novel and simple biomarkers that can better predict persistent organ failure (OF). Lipoproteins, especially high-density lipoprotein (HDL), and apolipoprotein A-I (APO A-I), have been shown to have anti-inflammation effects in various clinical settings. Severe acute pancreatitis (SAP) is associated with hypo-lipoproteinemia. We studied whether the concentrations of HDL and APO A-I can predict persistent OF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 39 publications
4
60
2
Order By: Relevance
“…There are notifications that inflammatory cytokines induced hepatic synthesis of acute phase proteins and low level of HDL is associated with high levels of inflammatory cytokines. It has been suggested that high levels of inflammatory cytokines impaired biosynthesis of HDL and also facilitated degradation of lipoprotein (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are notifications that inflammatory cytokines induced hepatic synthesis of acute phase proteins and low level of HDL is associated with high levels of inflammatory cytokines. It has been suggested that high levels of inflammatory cytokines impaired biosynthesis of HDL and also facilitated degradation of lipoprotein (45).…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis (AP) is noninfectious inflammatory disorder of pancreas representing variable severity ranging from mild to severe inflammatory cascade associated with multipleorgan failure. (38,45). The incidence of this disease is increasing in the worldwide (11).…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of HDL have been associated with poor short‐term outcomes (i.e. higher mortality rates , organ failure development and greater length of ICU stay ) in patients with established septic shock and other acute disorders, such as pancreatitis and burn‐injured patients . However, very few studies have investigated the relationship between HDL at presentation and the development of sepsis‐associated AKI , nor have the factors involved in decreased eGFR after an episode of sepsis been completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…It is still a great challenge to quickly and effectively screen out AP patients with high risk of persistent organ failure during clinical management. Previous reports have shown that many biomarkers such as triglycerides, high-density lipoprotein, and apolipoprotein A could be important predictors of persistent organ failure in AP patients [1,2].…”
Section: Introductionmentioning
confidence: 99%